Total productive maintenance - Masterson, William F.; Bollinger, Steven R. (Manufacturing insights)
This program demonstrates how predictive and preventive maintenance techniques can bring an end to crisis maintenance. It shows how TPM keeps equipment operating at design specs, and gets more output from smaller facilities.